2022
DOI: 10.1177/17423953211073368
|View full text |Cite
|
Sign up to set email alerts
|

Navigational health literacy among people with chronic illness

Abstract: Objectives People with chronic illness are particularly dependent on navigating and using the health care system. This requires navigational health literacy (HL-NAV). The article aims to examine the distribution and predictors of HL-NAV in a sample of chronically ill individuals. Methods Data of 1,105 people with chronic illness from the general population in Germany were collected in December 2019 and January 2020. HL-NAV was assessed by 12 items (score 0–100). Bivariate and multiple linear regression analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…In particular, this applies to frequent users of the HCS and their significant others, especially to people with chronic illness who naturally have more health care needs; needs that change frequently, become more complex over time, and which may include multiple layers of health care [ 25 , 26 , 27 , 28 , 29 ]. In consequence, they are particularly exposed to the HCS and must continually acquaint themselves with new health care settings and services, making them especially reliant on adequate NAV-HL [ 30 ]. NAV-HL may also matter since low HL has been identified as a barrier for understanding and using the HCS, as supporting an inappropriate use of health care services, and as a cause of potentially higher health expenditure [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, this applies to frequent users of the HCS and their significant others, especially to people with chronic illness who naturally have more health care needs; needs that change frequently, become more complex over time, and which may include multiple layers of health care [ 25 , 26 , 27 , 28 , 29 ]. In consequence, they are particularly exposed to the HCS and must continually acquaint themselves with new health care settings and services, making them especially reliant on adequate NAV-HL [ 30 ]. NAV-HL may also matter since low HL has been identified as a barrier for understanding and using the HCS, as supporting an inappropriate use of health care services, and as a cause of potentially higher health expenditure [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, following the relational model of HL—describing HL as the result of individual skills and abilities, but also of the demands and complexity individuals face in dealing with health information [ 33 ]—the low availability and comprehensibility of navigation-related information led to the hypothesis of poorly developed NAV-HL in general populations. Navigation-related information usually meets criteria relevant to organizations within the HCS but does not sufficiently consider challenges faced by its users [ 30 , 34 , 35 ], i.e., it is characterized by low user orientation and usability.…”
Section: Introductionmentioning
confidence: 99%
“…During a quick review of the titles and abstracts of the included articles, we identified and included 6 additional relevant publications using the “link to similar articles” browser in PubMed. The PRISMA protocol (Preferred Reporting Items for Systematic Review and Meta-Analysis) was used to display the results of the literature review ( 14 ) ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The health literacy concept in general concerns general health-related competencies, but if we want to study and measure literacy in relation to specific health contexts, fields, topics, and even diseases, these forms of health literacy require more exact definitions; conceptualizations with regard to specific issues. Many forms of health literacy have been already defined and studied, such as navigational health literacy ( 14 ), communicative health literacy with physicians ( 8 ), pharmaceutical literacy ( 15 ), diabetes (health) literacy ( 16 ), to name just a few. All of these context-specific health literacies deserve more attention.…”
Section: Context Specific Conceptualizations Of Health Literacy and I...mentioning
confidence: 99%